Intention of electronic filing usage by salaried taxpayers in Malacca / Nurul Nadiah Ibrahim - Ibrahim, Nurul Nadiah (2015)
E-filing has been implemented since 2006, but after ten years, some taxpayers are still submitting income tax return through manual tax filing. This is proven by the statistics from the IRBM, which indicates that only 80% of taxpayers in Malaysia have adopted the e-filing tax system in 2013 (IRBM, 2013).The remaining 20 percent that still use manual tax filing could creates concern. Thus, the purpose of this study is to examine the factors that will influence taxpayers' intention to use or continue using e-filing. A questionnaire survey was personally distributed to 210 teachers from seven secondary schools in Melaka Tengah District within a two-month period (October 2015 to November 2015). In total, 151 usable questionnaires were collected, which is a response rate of 71.9%. The data were analysed using multiple regression and it was found that self-efficacy, perceived usefulness, perceived ease of use and social norm, significantly influence the intentions of teachers in secondary schools to use or continue using e-filing system. This study contributes to better understanding on the level of intention to use or continue using the e-filing system by teachers from secondary schools in Melaka Tengah District and proved that factors that have been highlighted by previous studies really contribute towards taxpayers' intentions to use e-filing. The findings are expected to contribute to the academic knowledge.